Influence of External Workforce Diversity Factors on Labor Productivity in Construction Projects: Empirical Evidence from Pakistan - Maqsoom, A. (Institute of Electrical and Electronics Engineers Inc., 2020)
Workforce diversity has grown into an imperative problem throughout the world as it is deeply connected to organizational performance. This indicates that the organization should be enhanced and competitive in the current global environment. To enter the international arena, workforce diversity is among fundamental solutions. The organization must utilize or spend essential reserves on workforce diversity to generate chances for optimum employee productivity. Various workforce diversity factors influence employee productivity, thus influencing the organizational performance and the built environment. This research aims to analyze the location, physical ability, ethnicity, and labor union related workforce diversity factors influencing labor productivity. Data was collected through on-site surveys by getting survey questionnaire filled by 131 management professionals employed at different project sites. Based on average MIR values, location and physical ability factors were characterized as most critical among the workforce diversity factors affecting the labor productivity. Also, it was identified that the labor productivity is highly reliant on the location of the workplace, the environment provided, the physical ability of a worker, cultural norms and lockdown effects particularly. This research involves the participants from the construction industry of Pakistan; the potential research can be extended to further service sectors and growing economies. Â© 2020 IEEE.